64.7k views
0 votes
Which expression is equivalent to (4 + 6i)2? –20 + 48i 8 + 12i 16 – 36i 20 + 48i

2 Answers

2 votes

Answer:

A -20+28i

Explanation:

User Oliver Rice
by
6.2k points
3 votes

Answer: Choice A) -20+48i

========================================

Work Shown:

x = (4+6i)^2

x = (4+6i)(4+6i)

x = y(4+6i) ...... let y = 4+6i

x = 4(y)+6i(y) ..... distribute

x = 4(4+6i)+6i(4+6i) .... plug in y = 4+6i

x = 16+24i+24i+36i^2 ..... distribute again

x = 16+24i+24i+36(-1) .... use the fact that i^2 = -1

x = 16+24i+24i-36

x = 16-36+24i+24i

x = -20+48i

User Bandon
by
5.8k points